2019
DOI: 10.4314/ahs.v19i3.44
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic pollutants in edible grasshoppers (Ruspolia nitidula) of Uganda and their major public health implications

Abstract: Background: Inorganic contamination of food products is associated with adverse health effects, however, information on grasshoppers in Africa is sparse. The objective of the study was to determine antioxidant, heavy metal and food safety status of edible grasshoppers of Uganda.Methods: A cross-sectional study was conducted in central and southwestern Uganda, in which a questionnaire was administered to grasshopper harvesters. Grasshopper samples were collected from each harvesting point and analyzed in the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, the THQ values were less than 1, implying that consumption of wild vegetables does not pose a long-term deleterious effect in children and adults. The high concentration of Pb in the edible wild plants could be due to soil contaminations from the metal residues resulting from the on-going irrational use of pesticides [ 65 ] or the use of heavy weapons during the 25 years of insurgency in the study area. Plant species in areas affected by military activities are known to accumulate heavy metals [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the THQ values were less than 1, implying that consumption of wild vegetables does not pose a long-term deleterious effect in children and adults. The high concentration of Pb in the edible wild plants could be due to soil contaminations from the metal residues resulting from the on-going irrational use of pesticides [ 65 ] or the use of heavy weapons during the 25 years of insurgency in the study area. Plant species in areas affected by military activities are known to accumulate heavy metals [ 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, through these, grasshoppers have become exposed to pesticide residues and other contaminants. In a study by Kasozi et al (2019) atomic absorbance spectrometric (AAS) method revealed high exposure of wild harvested grasshoppers to heavy metals particularly lead, beyond acceptable safe limits. The heads of R. differens samples from Central Uganda had heavier concentration, believed to be from vegetation exposed to pesticides.…”
Section: Hazards Associated With R Differensmentioning
confidence: 99%
“…Pesticide residues and toxic metals in reared insects can be associated with particular insect species, their source before being reared, the source and type of substrates used and contamination of the rearing unit [2,39]. For instance, the bioaccumulation of cadmium has been reported in crickets and the black soldier fly (Hermetia illucens), as has arsenic in yellow mealworms (Tenebrio molitor) and lead in R. differens [39,41,42]. Prior to consumption, edible insects should not exceed certain maximum permissible levels of heavy metals (lead, cadmium, arsenic and mercury) and trace metals (iron, manganese, copper and magnesium) [2].…”
Section: Pesticide Residues and Toxic Trace Metalsmentioning
confidence: 99%